ANTECEDENTS OF STOCK INVESTMENT INTENTION AMONG GENERATION Z - Anjelika Natasyah; Ali Wardhana (Sampoerna University, 2026)
This study examines how financial literacy, attitude toward investment, subjective norms, and perceived behavioral control relate to stock investment intention among Generation Z. A quantitative survey design was used, with data gathered from 222 Generation Z respondents through purposive sampling and analyzed with Structural Equation Modeling-Partial Least Squares (SEM-PLS) in SmartPLS 4.0. Attitude toward investment, subjective norms, and perceived behavioral control each showed a positive and significant relationship with investment intention, and financial literacy likewise had a significant effect. The results add to what is known about financial management among younger investors and offer a point of reference for investors, financial institutions, and researchers examining the drivers of stock investment intention.